Criminal Liability Of Perpetrators Of Illegal Medical Practices (Perspective Of Law Number 17 Of 2023 Concerning Health) - Muhammad Reski Ansyah; Abdul Razak Nasution (LAWYER: Jurnal Hukum, 2023)
In connection with this, Legislation in the Health Sector was made. Based on Article 1 paragraph (1) of Permenkes No. 2052/MenKes/Per/X/2011 concerning Practice Permits and Implementation of Medical Practices, "Medical practice is a series of activities carried out by doctors against patients in carrying out health efforts". The doctor has a Registration Certificate (STR) or has officially held the profession of doctor, dentist, specialist doctor, specialist dentist. After having an STR, a doctor who wants to practice medicine is required to have a Practice License (SIP). The obligation to have a SIP is contained in Permenkes No. 2052/MenKes/Per/X/2011 concerning Practice License and Implementation of Medical Practice. This research uses normative juridical research, as for what is meant by the type of normative juridical research is library legal research because in normative legal research is carried out by examining library materials or secondary data only, where the data collection tool used in research is by library research. The results of this study are that the legal relationship between doctors and patients is regulated by law as an agreement. As a result, doctors are required to carry out the object of the agreement in accordance with their professional expertise. As a result, doctors are required to carry out the object of the engagement in accordance with their professional expertise. As a result, a doctor can be held legally liable in both criminal and civil courts. In terms of criminal law, a doctor who does not carry out his duties and profession in accordance with the procedure may be subject to a number of provisions of the Criminal Code, especially due to negligence resulting in the death of the patient.